Pengaruh Perubahan Tarif Terhadap Jumlah Penumpang Angkutan Udara - Lukiana Lukiana (Research and Development Agency of The Ministry of Transportation, 2010)
Demand for transport is an indirect request (derived demand) means journey is not done solely for the trip it self but because of the needs that must be met in the course. Demand for transport is influenced by many factors directly related to transportation or not. These factors are always changing along with the dynamics of society and the passage of time. With the changes in factors, transport demand would be changing.Changes in demand will be increased or decreased depending on the nature of these factors in influencing demand. By using exponential regression will know the level of change in the number of passengers Mataram-Jakarta route. The result showed that the elasticity of transport demand for Mataram-Jakarta route is -0.04. The fast time travel is a dominant factor affecting of the air transport mode choice, followed by comfort, tariffs and no one chose the factor of safety. In case of price increase some of air would be switch to alternative mode such buses.